Palestine and Israel disputes: issues and challenges - Eishan Jan, Mohammad Naqib (2016)
The Palestine issue is a politico-legal issue that has remained unresolved for so long. The issue started immediately after the disintegration of the Ottoman Empire and following the occupation of Palestine by Great Britain. Britain, in disregard of the will of the majority in Palestine, facilitated Jewish settlements, supported foreign- led Zionist movement, fulfilled its unjust promise as contained in the Balfour Declaration of 1917 and created a state for Jews in Palestine. Britain by doing this further complicated the issue – an issue which the League of Nations was unable to solve and it has remained as the most serious unresolved issue on the agenda of the UN since its establishment.